Objective, Quantitative, Data-Driven Assessment of Chemical Probes. Issue 2 (15th February 2018) - Antolin, Albert A.; Tym, Joseph E.; Komianou, Angeliki; Collins, Ian; Workman, Paul; Al-Lazikani, Bissan
Summary: Chemical probes are essential tools for understanding biological systems and for target validation, yet selecting probes for biomedical research is rarely based on objective assessment of all potential compounds. Here, we describe the Probe Miner: Chemical Probes Objective Assessment resource, capitalizing on the plethora of public medicinal chemistry data to empower quantitative, objective, data-driven evaluation of chemical probes. We assess >1.8 million compounds for their suitability as chemical tools against 2, 220 human targets and dissect the biases and limitations encountered. Probe Miner represents a valuable resource to aid the identification of potential chemical probes, particularly when used alongside expert curation. Graphical Abstract: Highlights: Systematic analysis of chemical probes uncovers new insights and limitations Novel data-driven scoring enables objective assessment of chemical probes A public, regularly updated resource equips researchers to evaluate probes Used alongside expert curation, provides a powerful resource for probe selection Abstract : Chemical probe selection remains largely subjective, not utilizing extensive medicinal chemistry data, causing widespread use of flawed probes. Antolin et al. describe the Probe Miner resource, empowering objective, quantitative, data-driven assessment of chemical probes based on regularly updated large-scale data.